أهمية التوسع في الإفصاح المحاسبي عن المسؤولية الإجتماعية لتحسين المعلومات المحاسبية - مازري ،الياس; عوينات ،فريد (جامعة الوادي University of Eloued, 2024)
هدفت هذه الدراسة الى معرفة مدى أهمية التوسع في الإفصاح المحاسبي عن المسؤولية الإجتماعية لتحسين جودة المعلومات المحاسبية، دراسة حالة "المديرية الجهوية للخدمات الإجتماعية سوناطراك ناحية بسكرة " التي تضم 15 فرع، حيث تم إستخدام البيانات الخاصة بالتقارير السنوية لهئية الخدمات الإجتماعية وذلك بالإعتماد على تحليل البيانات وكذا مقابلة مع مسؤول مصلحة المالية والمحاسبة. حيث خلصة هذه الدراسة الى أن إدخال محاسبة المسؤولية الإجتماعية في قوائم مالية ذات طابع إقتصادي وإجتماعي زاد من جودة المعلومات المحاسبية واعطى مخرجات ذات مصداقية، كما نوصي بضرورة إصدار قوانين وتشريعات تلزم الشركات الجزائرية بالتوسع في الإفصاح المحاسبي، ليصبح إفصاحا شاملا وإلزاميا لمواجهة التحديات والمشاكل المحاسبية المعاصرة. This study aimed to determine the extent of the importance of expanding accounting disclosure of social responsibility to improve the quality of accounting information. A case study of the Regional Directorate of Social Services Sonatrach in the Biskra region, which includes 16 branches, where data from the annual reports of the Social Services Authority was used, based on data analysis as well as an interview. With the official of the Finance and Accounting Department. The conclusion of this study is that introducing social responsibility accounting into financial statements of an economic and social nature increased the quality of accounting information and gave credible outputs.We also recommend the necessity of issuing laws and legislation requiring Algerian companies to expand accounting disclosure, so that it becomes comprehensive and mandatory disclosure to confront contemporary accounting challenges and problems.
The importance of expanding accounting disclosure of social responsibility to improve accounting information - Case Study of the regional Directorate of Social ServicesSonatrach in BISKRA –
Keywords: التوسع في الإفصاح المحاسبي; الموثوقية; المعلومات المحاسبية; محاسبة المسؤولية الإجتماعية; Expanding accounting disclosure; reliability; accounting information; social responsibility accounting